No Genetic Causal Association Between Periodontitis and Arthritis: A Bidirectional Two-Sample Mendelian Randomization Analysis - Yin, Kang-Jia; Huang, Ji-Xiang; Wang, Peng; Yang, Xiao-Ke; Tao, Sha-Sha; Li, Hong-Miao; Ni, Jing; Pan, Hai-Feng (Frontiers in Immunology, 2022)
Periodontitis (PD) has been linked to arthritis in previous epidemiological observational studies; however, the results are inconclusive. It remains unclear whether the association between PD and arthritis is causal. The purpose of this study was to investigate the causal association of PD with arthritis, including rheumatoid arthritis (RA) and osteoarthritis (OA). We performed a two-sample bidirectional Mendelian randomization (MR) analysis using publicly released genome-wide association studies (GWAS) statistics. The inverse-variance weighted (IVW) method was used as the primary analysis. We applied four complementary methods, including weighted median, weighted mode, MR-Egger regression and MR pleiotropy residual sum and outlier (MR-PRESSO) to detect and correct for the effect of horizontal pleiotropy. Genetically determined PD did not have a causal effect on OA (OR = 1.06, 95% CI: 0.99-1.15, P = 0.09) and RA (OR = 0.99, 95% CI: 0.87-1.13, P = 0.89). Furthermore, we did not find a significant causal effect of arthritis on PD in the reverse MR analysis. The results of MR-Egger regression, Weighted Median, and Weighted Mode methods were consistent with those of the IVW method. Horizontal pleiotropy was unlikely to distort the causal estimates according to the sensitivity analysis. Our MR analysis reveals non-causal association of PD with arthritis, despite observational studies reporting an association between PD and arthritis.